ANALISIS PENGARUH ALIASING TERHADAP LAGU HATI-HATI DI JALAN OLEH TULUS MENGGUNAKAN MATLAB - Mutia Istiqomah (Telecommunications, Networks, Electronics, and Computer Technologies (TELNECT), 2023)
This research aims to analyze the influence of aliasing on the song Hati-Hati di Jalan by Tulus, using MATLAB software. Aliasing is a phenomenon that occurs when the frequency of the original signal exceeds half of the sampling frequency. In this study, the song Hati-Hati di Jalan is represented as a digital audio signal reconstructed using sampling techniques with various sampling frequencies. The research method consists of several steps. First, the Hati-Hati di Jalan song is imported into MATLAB as an audio file. Then, the audio signal is sampled at different sampling frequencies, including frequencies below and above the Nyquist frequency. Subsequently, an analysis is conducted on the sampling results using MATLAB tools. The analysis results indicate the influence of aliasing on the Hati-Hati di Jalan song when the sampling frequency does not meet the Nyquist criteria. Aliasing is observed in the form of improper frequency distortion, causing frequency shifting and stacking. This aliasing phenomenon can alter the original characteristics of the song and affect the perceived audio quality. This research provides a deeper understanding of the influence of aliasing on a song using MATLAB as an analysis tool. These findings can serve as a guideline to avoid aliasing in audio sampling processes and ensure accurate reproduction. Additionally, this study offers insights into the importance of selecting the appropriate sampling frequency to maintain optimal audio quality.